2011
DOI: 10.2147/ndt.s26403
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of adverse drug reactions reported for attention deficit hyperactivity disorder (ADHD) medications in the pediatric population: a qualitative review of empirical studies

Abstract: BackgroundTo review empirical studies of adverse drug reactions (ADRs) reported to be associated with the use of medications generally licensed for treatment of attention deficit hyperactivity disorder (ADHD) symptoms in the pediatric population.MethodsPubMed, Embase, and PsycINFO® databases were searched from origin until June 2011. Studies reporting ADRs from amphetamine derivates, atomoxetine, methylphenidate, and modafinil in children from birth to age 17 were included. Information about ADR reporting rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Therefore, the results cannot be attributable to one form of medication alone, and as a result of clinical (ie, adverse side effects) and personal decisions (ie, a desire to withdraw), some participants were unable to adhere to long-term treatment arms 62. Following their review of adverse events in studies lasting from 1 to 32 weeks, Aagaard and Hansen63 concluded that there was a lack of good evidence about adverse effects during long-term medication use.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results cannot be attributable to one form of medication alone, and as a result of clinical (ie, adverse side effects) and personal decisions (ie, a desire to withdraw), some participants were unable to adhere to long-term treatment arms 62. Following their review of adverse events in studies lasting from 1 to 32 weeks, Aagaard and Hansen63 concluded that there was a lack of good evidence about adverse effects during long-term medication use.…”
Section: Discussionmentioning
confidence: 99%
“…differences in appetite suppression between stimulants. 78 Switching from stimulants to atomoxetine is more likely to address the concern and may be tried as an alternative to switching between stimulants or as next step. Bupropion is also effective for ADHD both in youth 79 and adults.…”
Section: Switching Adhd Medications Due To Weight-loss Concernsmentioning
confidence: 99%
“…Despite this, most published adverse drug reactions have not been serious [74,75], and the use of modafinil has been reported in the treatment of EDS in narcoleptic children [60,76,77]. Off-label use of the drug has also been reported in ADHD to be effective and well tolerated [78][79][80][81].…”
Section: Narcolepsymentioning
confidence: 99%